Plumbagin Enhances the Radiosensitivity of Tongue Squamous Cell Carcinoma Cells via Downregulating ATM. (27th August 2021) - Pan, Shu-Ting; Huang, Gan; Wang, Qiaohong; Qiu, Jia-Xuan
Abstract : This study was designed to investigate whether plumbagin (PL) could sensitize ionizing radiation (IR) in tongue squamous cell carcinoma (TSCC) cells and its possible mechanisms. Cell proliferation and combination index analysis was based on MTT and colony formation assay. Flow cytometry was applied to analyze the cell cycle distribution and apoptosis after the treatment of PL and/or IR. RT-PCR was used to examine the gene expression level of ataxia telangiegatasiata muted (ATM) and nuclear factor kappa beta (NF-κB ) after various treatment groups. Western blot was used to examine the protein level of ATM and NF-κB as well as their phosphorylation level. PL enhances the cytotoxicity of IR in TSCC cells. Combination index was <1 which represents a synergistic effect. Combined PL and IR promoted G2/M arrest and apoptosis which could be reversed by ATM activator chloroquine phosphate. ATM and NF-κB were both inhibited by PL and IR combination. PL can efficiently enhance the radiosensitivity of TSCC cells by inducing G2/M arrest and apoptosis via downregulating ATM.